A method for preparing high-strength anti-fogging fluoroplastic film
By performing corona treatment on the ETFE film and spraying anti-fog coating with specific formulas, the problem of water droplets and dripping in the film during the seasons of large temperature differences is solved, high-intensity and good anti-fog effect are achieved, and light transmission performance and stability of the plant growth environment are improved.
Patent Information
- Application Number
- CN202510285957.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In seasons with large temperature differences, ETFE films are prone to water droplet formation and dripping, which affects light transmission performance and plant growth.
The high-strength anti-fogging fluoroplastic film preparation method is adopted. By melting and stirring the fluoroplastic particles evenly, a plastic film substrate is formed, and anti-fogging coating is sprayed on the surface of the substrate after corona treatment. The coating formula includes silicon sol, boehmite, triglyceride, sorbitol beanoleate, fluorocarbon surfactant, polyurethane, polymethyl methacrylate and paraffin.
It achieves high-intensity and good anti-fogging effect, prevents fogging on the surface of the film, and improves light transmission performance and stability of the plant growth environment.
Smart Images

Figure CN119775619A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluoroplastic films and relates to a method for preparing a high-strength anti-fogging fluoroplastic film. Background Art
[0002] ETFE film is often used in outdoor buildings, such as membrane structures and greenhouses, because of its excellent weather resistance and non-stick surface properties. In seasons with large temperature differences, such as winter, water droplets are easily formed on the surface of the film due to the large temperature difference between indoor and outdoor, affecting its light transmission performance. After the water droplets accumulate, they will also drip from the surface of the film, causing dripping. Especially when used as a greenhouse film, the decrease in light transmittance will affect the growth of plants, and water droplets dripping from the surface of the film will also drip on the plants, affecting the growth of crops. It is necessary to develop a fluoroplastic film with anti-fogging properties to prevent the film surface from fogging. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a high-strength anti-fogging fluoroplastic film, which has the characteristics of high strength and good anti-fogging effect.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a high-strength anti-fogging fluoroplastic film, the specific process of the fluoroplastic film preparation method is as follows: S1: Put the fluoroplastic particles into a mixing and stirring machine, heat to 260-280°C to make the fluoroplastic particles molten, and stir at a speed of 300 r / min for 3-4 hours to obtain a uniformly mixed melt; S2: Extruding the melt through an extruder, cooling and forming, obtaining a plastic film substrate, performing corona treatment on the surface of the substrate, spraying a layer of anti-fog coating evenly on the surface of the substrate after the corona treatment, and drying to obtain the fluoroplastic film; The formula of the anti-fog coating is as follows: by weight, 10-15 parts of silica sol, 5-10 parts of boehmite, 2-5 parts of triglyceride, 2-5 parts of sorbitan oleate, 1-3 parts of fluorocarbon surfactant, 5-10 parts of polyurethane, 5-10 parts of polymethyl methacrylate, 5-10 parts of paraffin, and 50-60 parts of deionized water. The preparation method of the anti-fog coating is as follows: S2.1: Grind the boehmite in a ball mill at a speed of 600 r / min for 2 h, disperse it in silica sol after grinding, and stir it at a speed of 150 r / min for 0.5-1 h to obtain a solid-liquid mixture A; S2.2: Heat the polyurethane to 170-190°C, stir it in a mixer at a speed of 300 r / min for 1-2 h after the temperature is constant, then increase the mixer speed to 400 r / min, add polymethyl methacrylate, and continue stirring for 2 h to obtain a uniform mixture B; S2.3: triglyceride and sorbitan oleate were mixed in a mass ratio of 1:1, and stirred at 40°C and 150 r / min for 2 h to obtain a mixture C; S2.4: Add the solid-liquid mixture A and the mixture C to the mixture B, stir at a speed of 350 r / min in a mixing mixer, control the temperature at 80-100°C during the process, and continue stirring for 3 h to ensure that the mixture C and the mixture B are fully blended to obtain a uniform mixture D; S2.5: Add fluorocarbon surfactant and paraffin to mixture D. During the addition process, adjust the stirrer speed to 450 r / min and control the temperature at 70-90 °C. Continue stirring for 2 h to obtain a uniform mixture E. S2.6: Slowly add deionized water to the mixture E, and adjust and reduce the speed of the stirrer to 300 r / min. After the addition is completed, continue stirring for 1 hour. After stirring, filter with gauze to obtain the anti-fog coating.
[0005] Furthermore, the fluoroplastic particles in S1 are ethylene-tetrafluoroethylene copolymer (ETFE).
[0006] Furthermore, the parameters of the corona treatment in S2 are an electrode gap of 1-2 mm, a power of 10-20 kW, and a voltage of 10000-20000 V.
[0007] Furthermore, the spraying parameters in S2 are a spraying distance of 40 mm and a spraying rate of 60 mm / s.
[0008] Furthermore, the drying parameters in S2 are a temperature of 80-90° C. and a duration of 8-10 hours.
[0009] Furthermore, the thickness of the fluoroplastic film prepared in S2 is 150 μm.
[0010] Furthermore, the silica sol in S2 is alkaline silica sol with a purity of 40%.
[0011] Furthermore, the boehmite obtained by grinding in S2.1 has a particle size of 800 mesh.
[0012] Furthermore, the rate of adding deionized water in S2.6 is 20 mL / min.
[0013] Furthermore, in S2.6, 500-mesh gauze is used for filtering.
[0014] In the anti-fog coating of the present invention, silica sol, boehmite, polyurethane and polymethyl methacrylate form the main structure of the coating, providing excellent adhesion and durability. Triglyceride, sorbitan oleate and fluorocarbon surfactant enhance the workability and stability of the coating by reducing surface tension, improving wettability and dispersibility. The addition of paraffin further improves the hardness and glossiness of the coating, while deionized water is used as a solvent to ensure uniform mixing of the components and stable performance of the coating.
[0015] As an important component of the coating, silica sol can enhance the adhesion and durability of the coating, has good suspension and dispersibility, prevents the precipitation of pigments and fillers, and improves the storage stability of the coating. Silica sol can chemically react with organic groups in the coating to form chemical bonds, thereby enhancing the bonding between the coating and the substrate. The present invention uses alkaline silica sol with a purity of 40%. The alkalinity of the alkaline silica sol can improve the catalytic activity of the reaction system, and is helpful for the chemical reaction and cross-linking curing of other components in the coating, thereby improving the performance and stability of the coating. The alkaline silica sol has a small particle size and high transparency, which can significantly improve the transparency and gloss of the coating. At the same time, its excellent fire resistance and heat insulation can also improve the high temperature resistance of the coating. In addition, the alkaline silica sol has high stability and is not easy to agglomerate and precipitate, thereby ensuring the stability of the coating during storage and use.
[0016] Boehmite has high hardness and wear resistance, and plays a filling and reinforcing role in coatings, enhancing the hardness and durability of the coating and improving the overall performance of the coating. Both silica sol and boehmite are usually used as inorganic nanoparticles in coatings to enhance the roughness and mechanical properties of the coating. They can form good chemical bonds with organic components and provide the hardness and wear resistance required for the coating.
[0017] Triglyceride has good dispersibility, which helps to evenly distribute pigments and fillers, and can also improve the wettability and adhesion of the coating to the substrate by reducing surface tension; triglyceride and sorbitol oleate are both surfactants, and have a hydrophilic head and a hydrophobic tail structure. They can form tiny hydrophilic areas in the coating, which helps to adsorb and disperse water molecules and prevent them from aggregating into water droplets. In addition, triglyceride and sorbitol oleate can improve the dispersibility of each component in the coating, and ensure that inorganic nanoparticles silica sol, boehmite and organic film-forming substances polyurethane and polymethyl methacrylate are evenly distributed in the coating, which helps to form a more uniform and dense coating and improve the anti-fog performance and durability of the coating. The present invention mixes triglyceride and sorbitol oleate in a mass ratio of 1:1. As an ester substance, triglyceride may play a role in lubrication, plasticization or regulating the fluidity of the coating in the coating, but when used alone, there may be limitations such as insufficient stability or affecting other properties of the coating. As a surfactant, sorbitan oleate has good dispersing and emulsifying properties, which helps to evenly disperse and stabilize the components in the coating, but it may not be enough to meet the specific performance requirements of the coating when used alone; mixing triglycerides and sorbitan oleate in a mass ratio of 1:1 can combine the advantages of both, improve the stability and uniformity of the coating, and adjust the fluidity of the coating, thereby making up for the limitations of using them alone. This mixed use can make the coating have better anti-fog performance, higher gloss, better weather resistance and construction performance. Triglycerides and sorbitan oleate have certain similarities in chemical structure, but there are also differences. This difference enables them to produce a synergistic effect when used together, thereby enhancing the overall performance of the coating. This synergistic effect can improve the uniformity of the coating, improve the anti-fog effect, and enhance the adhesion of the coating to the substrate. By mixing triglycerides and sorbitan oleate, the rheological properties of the coating can be optimized, making it easier to operate and control during construction. At the same time, mixed use can also improve the flexibility and impact resistance of the coating, and improve the durability and service life of the coating.
[0018] Fluorocarbon surfactants have excellent leveling and wetting properties, and can enhance the flatness and brightness of the paint surface. Fluorocarbon surfactants have stable high-temperature performance and are suitable for use in high-temperature baking and high-temperature dipping coating processes. In addition, the addition of fluorocarbon surfactants can significantly improve the wetting, penetration, emulsification and leveling properties of the medium, making the coating have excellent water-repellent, oil-repellent and anti-fouling functions. Fluorocarbon surfactants have extremely low surface energy and can further enhance the hydrophobic properties of the coating. In anti-fog coatings, it helps to make the coating surface smoother and reduce the adhesion of water droplets, thereby achieving an anti-fog effect. In this formula, it can work synergistically with the hydrophilic component to form a balance to optimize the anti-fog performance; Polyurethane can form a uniform coating covering the surface of the substrate. Polyurethane also has high water resistance and corrosion resistance, which helps prevent water vapor condensation and plays an anti-fog role. Polymethyl methacrylate is a highly transparent material that helps to improve the transparency and glossiness of the coating. It also has good chemical stability and can enhance the weather resistance and chemical corrosion resistance of the coating. Polyurethane and polymethyl methacrylate, both film-forming substances, are the main components of the coating. They can form a continuous and uniform coating and fix other active ingredients on the surface of the substrate. Both polyurethane and polymethyl methacrylate have good water resistance and weather resistance and can protect the coating from damage for a long time.
[0019] Adding paraffin as an additive can increase the hardness and wear resistance of the coating. Paraffin can form a thin film on the surface of the coating to reflect light and increase the gloss of the coating. In addition, it can also enhance the sealing of the coating, prevent moisture intrusion, and improve anti-fog performance.
[0020] ETFE in the present invention was purchased from Wuhan Hongde Yuexin Pharmaceutical Technology Co., Ltd. with a purity of 99%; alkaline silica sol with a purity of 40% in the present invention was purchased from Jinan Feiyue Chemical Co., Ltd.; boehmite in the present invention was purchased from Shanghai Buwei Applied Materials Technology Co., Ltd. with a purity of 99.9%; triglycerides in the present invention were purchased from Hubei Chengfeng Chemical Co., Ltd. with a purity of 99%; sorbitan oleate in the present invention was purchased from Guangdong Runhua Chemical Co., Ltd. with a purity of 100%; fluorocarbon surfactant in the present invention was purchased from Shaanxi Aobo Lihui New Materials Technology Co., Ltd. with a purity of 99%; polyurethane in the present invention was purchased from Shenyang Yilepux Chemical Co., Ltd. with a purity of 99%; polymethyl methacrylate in the present invention was purchased from Wuhan Jixin Yibang Biotechnology Co., Ltd. with a purity of 99%; paraffin in the present invention was purchased from Maloya New Materials (Shanghai) Co., Ltd. with a purity of 99%.
[0021] Beneficial effects of the present invention: The invention first melts fluoroplastic particles at a high temperature of 260-280 DEG C, and stirs them at a rotation speed of 300 r / min for 3-4 hours, thereby ensuring the full mixing and uniformity of the raw materials and providing a stable basis for subsequent processing; the plastic film substrate obtained by extruding and cooling the extruder has excellent physical properties and molding stability, and the corona treatment enhances the adhesion of the substrate surface, so that the anti-fog coating can be firmly attached to the substrate; in the preparation process of the anti-fog coating, various components are finely ground, stirred and mixed, thereby ensuring the uniformity and stability of the coating, wherein inorganic components such as silica sol and boehmite provide excellent weather resistance and wear resistance; organic components such as triglyceride and sorbitan oleate are helpful to form a smooth surface and reduce the attachment of water droplets; and the fluorocarbon surfactant further improves the anti-fog performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0023] Figure 1 Preparation process of fluoroplastic film with anti-fogging effect. DETAILED DESCRIPTION
[0024] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0025] Example 1 A method for preparing a high-strength anti-fogging fluoroplastic film, the specific process of the fluoroplastic film preparation method is as follows: S1: Put ETFE particles into a mixing and stirring machine, heat to 270°C to make the ETFE particles molten, and stir at a speed of 300 r / min for 3 hours to obtain a uniformly mixed melt; S2: extruding the melt through an extruder, cooling and forming, obtaining a plastic film substrate, performing corona treatment on the surface of the substrate, wherein the parameters of the corona treatment are an electrode gap of 2 mm, a power of 15 kW, and a voltage of 15000 V, and then spraying a layer of anti-fog coating evenly on the surface of the substrate after the corona treatment, wherein the spraying parameters are a spraying distance of 40 mm, a spraying rate of 60 mm / s, and performing a drying treatment at a temperature of 80° C. for 10 hours to obtain the fluoroplastic film, wherein the thickness of the obtained fluoroplastic film is 150 μm; The formula of the anti-fog coating is as follows: by weight, 15 parts of alkaline silica sol with a purity of 40%, 10 parts of boehmite, 3 parts of triglyceride, 3 parts of sorbitan oleate, 3 parts of fluorocarbon surfactant, 10 parts of polyurethane, 5 parts of polymethyl methacrylate, 10 parts of paraffin, and 50 parts of deionized water. The preparation method of the anti-fog coating is as follows: S2.1: Grind the boehmite in a ball mill at a speed of 600 r / min for 2 h, and the boehmite obtained by grinding has a particle size of 800 mesh. Disperse the ground boehmite in silica sol, and stir at a speed of 150 r / min for 0.5 h to obtain a solid-liquid mixture A; S2.2: Heat the polyurethane to 180°C, stir it in a mixer at a speed of 300 r / min for 2 h after the temperature is maintained constant, then increase the mixer speed to 400 r / min, add polymethyl methacrylate, and continue stirring for 2 h to obtain a uniform mixture B; S2.3: triglyceride and sorbitan oleate were mixed in a mass ratio of 1:1, and stirred at 40°C and 150 r / min for 2 h to obtain a mixture C; S2.4: Add the solid-liquid mixture A and the mixture C to the mixture B, stir at a speed of 350 r / min in a mixing mixer, control the temperature at 80°C during the process, and continue stirring for 3 hours to ensure that the mixture C and the mixture B are fully blended to obtain a uniform mixture D; S2.5: Add fluorocarbon surfactant and paraffin to mixture D. During the addition process, adjust the stirrer speed to 450 r / min and control the temperature at 80°C. Continue stirring for 2 h to obtain a uniform mixture E. S2.6: Slowly add deionized water to the mixture E at a rate of 20 mL / min, and adjust the speed of the stirrer to 300 r / min. After the addition is completed, continue stirring for 1 hour. After stirring, filter with 500 mesh gauze to obtain the anti-fog coating.
[0026] Example 2 A method for preparing a high-strength anti-fogging fluoroplastic film, the specific process of the fluoroplastic film preparation method is as follows: S1: Put ETFE particles into a mixing and stirring machine, heat to 260° C. to make the ETFE particles molten, and stir at a speed of 300 r / min for 4 hours to obtain a uniformly mixed melt; S2: extruding the melt through an extruder, cooling and forming, obtaining a plastic film substrate, performing corona treatment on the surface of the substrate, wherein the parameters of the corona treatment are an electrode gap of 1 mm, a power of 20 kW, and a voltage of 10000 V, and then spraying a layer of anti-fog coating evenly on the surface of the substrate after the corona treatment, wherein the spraying parameters are a spraying distance of 40 mm, a spraying rate of 60 mm / s, and performing a drying treatment at a temperature of 90° C. for 8 hours to obtain the fluoroplastic film, wherein the thickness of the obtained fluoroplastic film is 150 μm; The formula of the anti-fog coating is as follows: by weight, 10 parts of alkaline silica sol with a purity of 40%, 10 parts of boehmite, 5 parts of triglyceride, 5 parts of sorbitan oleate, 2 parts of fluorocarbon surfactant, 5 parts of polyurethane, 10 parts of polymethyl methacrylate, 7 parts of paraffin, and 55 parts of deionized water. The preparation method of the anti-fog coating is as follows: S2.1: Grind the boehmite in a ball mill at a speed of 600 r / min for 2 h, and the boehmite obtained by grinding has a particle size of 800 mesh. Disperse the ground boehmite in silica sol, and stir at a speed of 150 r / min for 1 h to obtain a solid-liquid mixture A; S2.2: Heat the polyurethane to 190°C, keep the temperature constant, and stir it in a mixer at a speed of 300 r / min for 1 hour, then increase the mixer speed to 400 r / min, add polymethyl methacrylate, and continue stirring for 2 hours to obtain a uniform mixture B; S2.3: triglyceride and sorbitan oleate were mixed in a mass ratio of 1:1, and stirred at 40°C and 150 r / min for 2 h to obtain a mixture C; S2.4: Add the solid-liquid mixture A and the mixture C to the mixture B, stir at a speed of 350 r / min in a mixing mixer, control the temperature at 80°C during the process, and continue stirring for 3 hours to ensure that the mixture C and the mixture B are fully blended to obtain a uniform mixture D; S2.5: Add fluorocarbon surfactant and paraffin to mixture D. During the addition process, adjust the stirrer speed to 450 r / min and control the temperature at 70°C. Continue stirring for 2 h to obtain a uniform mixture E. S2.6: Slowly add deionized water to the mixture E at a rate of 20 mL / min, and adjust the speed of the stirrer to 300 r / min. After the addition is completed, continue stirring for 1 hour. After stirring, filter with 500 mesh gauze to obtain the anti-fog coating.
[0027] Example 3 A method for preparing a high-strength anti-fogging fluoroplastic film, the specific process of the fluoroplastic film preparation method is as follows: S1: Put ETFE particles into a mixing and stirring machine, heat to 280°C to make the ETFE particles molten, and stir at a speed of 300 r / min for 3-4 hours to obtain a uniformly mixed melt; S2: extruding the melt through an extruder, cooling and forming, obtaining a plastic film substrate, performing corona treatment on the surface of the substrate, the corona treatment parameters are electrode gap 2mm, power 10kW, voltage 20000V, and then spraying a layer of anti-fog coating evenly on the surface of the substrate after the corona treatment, the spraying parameters are spraying distance 40mm, spraying rate 60mm / s, and drying at a temperature of 80°C for 10h to obtain the fluoroplastic film, and the thickness of the obtained fluoroplastic film is 150μm; The formula of the anti-fog coating is as follows: by weight, 10 parts of alkaline silica sol with a purity of 40%, 10 parts of boehmite, 2 parts of triglyceride, 2 parts of sorbitan oleate, 3 parts of fluorocarbon surfactant, 7 parts of polyurethane, 7 parts of polymethyl methacrylate, 10 parts of paraffin, and 60 parts of deionized water. The preparation method of the anti-fog coating is as follows: S2.1: Grind the boehmite in a ball mill at a speed of 600 r / min for 2 h, and the boehmite obtained by grinding has a particle size of 800 mesh. Disperse the ground boehmite in silica sol, and stir at a speed of 150 r / min for 1 h to obtain a solid-liquid mixture A; S2.2: Heat the polyurethane to 170°C, keep the temperature constant, and stir it in a mixer at a speed of 300 r / min for 2 h, then increase the mixer speed to 400 r / min, add polymethyl methacrylate, and continue stirring for 2 h to obtain a uniform mixture B; S2.3: triglyceride and sorbitan oleate were mixed in a mass ratio of 1:1, and stirred at 40°C and 150 r / min for 2 h to obtain a mixture C; S2.4: Add the solid-liquid mixture A and the mixture C to the mixture B, stir at a speed of 350 r / min in a mixing mixer, control the temperature at 100°C during the process, and continue stirring for 3 hours to ensure that the mixture C and the mixture B are fully blended to obtain a uniform mixture D; S2.5: Add fluorocarbon surfactant and paraffin to mixture D. During the addition process, adjust the stirrer speed to 450 r / min and control the temperature at 90°C. Continue stirring for 2 h to obtain a uniform mixture E. S2.6: Slowly add deionized water to the mixture E at a rate of 20 mL / min, and adjust the speed of the stirrer to 300 r / min. After the addition is completed, continue stirring for 1 hour. After stirring, filter with 500 mesh gauze to obtain the anti-fog coating.
[0028] Comparative Example 1 In this comparative example, no surface corona treatment was performed during the preparation process, and the remaining steps were consistent with those in Example 1.
[0029] Comparative Example 2 In this comparative example, boehmite was not added during the preparation of the anti-fog coating, and the remaining steps were consistent with those of Example 1.
[0030] Comparative Example 3 In this comparative example, no alkaline silica sol with a purity of 40% was added during the preparation of the anti-fog coating, and the remaining steps were consistent with those of Example 1.
[0031] Comparative Example 4 In this comparative example, no triglyceride was added during the preparation of the anti-fog coating, and the remaining steps were consistent with those of Example 1.
[0032] Comparative Example 5 In this comparative example, sorbitan oleate was not added during the preparation of the anti-fog coating, and the remaining steps were consistent with those of Example 1.
[0033] Comparative Example 6 In this comparative example, no fluorocarbon surfactant was added during the preparation of the anti-fog coating, and the remaining steps were consistent with those of Example 1.
[0034] Comparative Example 7 In this comparative example, polyurethane was not added during the preparation of the anti-fog coating, and the remaining steps were consistent with those of Example 1.
[0035] Comparative Example 8 In this comparative example, no paraffin was added during the preparation of the anti-fog coating, and the remaining steps were consistent with those of Example 1.
[0036] The anti-fogging performance of the embodiment and the comparative example was tested. The testing method was based on the standard GB / T 31726-2015. A sample of 300*160 mm was tested for anti-fogging performance using the water bath hot fog method. The strength test was performed based on the standard ISO 527-3-2018. The experimental results are summarized in the following table.
[0037] From the above experimental data, it can be seen that corona treatment of the substrate surface can make the coating better coated on the substrate surface, thereby effectively improving the anti-fogging performance and tensile strength of the fluoroplastic film. Adding boehmite, alkaline silica sol with a purity of 40%, and paraffin to the coating can effectively improve the strength of the fluoroplastic film, and the addition of fluorocarbon surfactants, paraffin, and the mixed use of triglycerides and sorbitan oleate can effectively improve the anti-fogging performance of the fluoroplastic film.
[0038] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-strength anti-fogging fluoroplastic film, characterized in that: The specific process of the fluoroplastic film preparation method is as follows: S1: Put the fluoroplastic particles into a mixing and stirring machine, heat to 260-280°C to make the fluoroplastic particles molten, and stir at a speed of 300 r / min for 3-4 hours to obtain a uniformly mixed melt; S2: Extruding the melt through an extruder, cooling and forming, obtaining a plastic film substrate, performing corona treatment on the surface of the substrate, spraying a layer of anti-fog coating evenly on the surface of the substrate after the corona treatment, and drying to obtain the fluoroplastic film; The formula of the anti-fog coating is as follows: by weight, 10-15 parts of silica sol, 5-10 parts of boehmite, 2-5 parts of triglyceride, 2-5 parts of sorbitan oleate, 1-3 parts of fluorocarbon surfactant, 5-10 parts of polyurethane, 5-10 parts of polymethyl methacrylate, 5-10 parts of paraffin, and 50-60 parts of deionized water. The preparation method of the anti-fog coating is as follows: S2.1: Grind the boehmite in a ball mill at a speed of 600 r / min for 2 h, disperse it in silica sol after grinding, and stir it at a speed of 150 r / min for 0.5-1 h to obtain a solid-liquid mixture A; S2.2: Heat the polyurethane to 170-190°C, stir it in a mixer at a speed of 300 r / min for 1-2 h after the temperature is constant, then increase the mixer speed to 400 r / min, add polymethyl methacrylate, and continue stirring for 2 h to obtain a uniform mixture B; S2.3: triglyceride and sorbitan oleate were mixed in a mass ratio of 1:1, and stirred at 40°C and 150 r / min for 2 h to obtain a mixture C; S2.4: Add the solid-liquid mixture A and the mixture C to the mixture B, stir at a speed of 350 r / min in a mixing mixer, control the temperature at 80-100°C during the process, and continue stirring for 3 h to ensure that the mixture C and the mixture B are fully blended to obtain a uniform mixture D; S2.5: Add fluorocarbon surfactant and paraffin to mixture D. During the addition process, adjust the stirrer speed to 450 r / min and control the temperature at 70-90 °C. Continue stirring for 2 h to obtain a uniform mixture E. S2.6: Slowly add deionized water to the mixture E, and adjust and reduce the speed of the stirrer to 300 r / min. After the addition is completed, continue stirring for 1 hour. After stirring, filter with gauze to obtain the anti-fog coating.
2. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The fluoroplastic particles in S1 are ethylene-tetrafluoroethylene copolymer (ETFE).
3. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The parameters of the corona treatment in S2 are an electrode gap of 1-2 mm, a power of 10-20 kW, and a voltage of 10000-20000 V.
4. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The spraying parameters in S2 are spraying distance 40 mm and spraying rate 60 mm / s.
5. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The drying parameters in S2 are: temperature 80-90° C., and time 8-10 hours.
6. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The thickness of the fluoroplastic film prepared in S2 is 150 μm.
7. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The silica sol in S2 is alkaline silica sol with a purity of 40%.
8. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The boehmite obtained by grinding in S2.1 has a particle size of 800 mesh.
9. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: The rate of adding deionized water in S2.6 is 20 mL / min.
10. The method for preparing a high-strength anti-fogging fluoroplastic film according to claim 1, characterized in that: In the above-mentioned S2.6, 500-mesh gauze is used for filtering.
Citation Information
Patent Citations
Hydrophobic and oleophobic silica-based translucent coating film and preparation method thereof
CN103951279A
Anti-ultraviolet and anti-fog polyethylene greenhouse film and preparation method thereof
CN111234366A
Agricultural anti-fogging film
JP1997076428A
Fluoro-saturated hydrocarbon group-containing compound, its production and surface treating agent and additive for coating material
JP2000256302A
JPH09522244A